Self-Stigma, Experiences and Psychological Conditions of Mothers Having Children with Malnutrition-Stunting: Literature Review - Ligar Tresna Darmawan Putri; Martha Irene Kartasurya; Syamsulhuda Budi Musthofa (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The problem of malnutrition and stunting is a trending global health problem that has a major impact on children's physical growth and cognitive development. The condition of the mother's mental and psychological well-being is an important substance that influences the mother's care in caring for stunted malnourished children. The mother's mental and psychological condition is related to the mother's self-acceptance. The mother's psychological dynamics are shown in the form of emotions such as anger, feeling offended, feeling embarrassed, and triggering stress because the mother is full of negative thoughts. The findings from this literature review explain the existence of unpleasant experiences while mothers care for their children. This unpleasant experience generally takes the form of words from health workers and questions from other people regarding their child's condition. Psychological and behavioral changes in mothers arise as a result of public stigma about stunted children which is seen as an indication of a lack of parental care, such as providing poor food which can risk lowering self-esteem and prevent mothers from accessing health services. Objective: This study aims to investigate in depth about the extent of the impact of self-stigma about having children with malnutrition or stunting on the psychological conditions that occur in mothers who have children with malnutrition or stunting. Method: This research uses a qualitative approach through a literature review method based on the PRISMA guide. Result: Based on several previous studies, negative community stigma regarding malnourished and stunted children has a significant impact on the psychological state of mothers. This is motivated by an unpleasant experience. There are several themes in the articles that have been reviewed. It was found that self-stigma is recognized by the perception of guilt, the concept of stigma is identified as the shame of having a child with nutritional deficiencies-stunting because they often get questions from others regarding their child's condition. The second theme is about the various psychological changes experienced by mothers. The third theme of self-stigma experienced by mothers significantly affect their behavior, often resulting in reluctance to seek health services for their children. Conclusion: The study cloncludes that self-stigma has a detrimental effect on the psychological conditions of mothers, leading to reduce health-seeking behavior and exacerbating the health issues of malnourished and stunted children. The findings underscore the need for interventions that address stigma, provide emotional support, and promote positive community attitudes towards malnutrition and stunting. It is necessary for health workers and cadres to convey information about stunting by conveying it in a kind and non-accusatory manner, and maintaining confidentiality about the child's condition by not being conveyed in public openly. In addition, to support mothers emotionally, it is necessary for health workers to develop education related to psychoeducation, counseling, promotion, emotional support, and home visits for mothers who are indicated to be absent from health services.